(untitled) (Sustainability in Debate, 2015)
E Carina H Keskitalo, org. Climate change and flood risk management - Adaptation and extreme events at the local level. Cheltenham, UK; Northampton, MA, USA: Edward Elgar Publishing, 2013. 321p. ISBN 987-1-78100-666-5. 135. Bibliografia, notas, índice remissivo e figuras.